Personalized Interpretation and Clinical Translation of Genetic Variants Associated With Cardiomyopathies - Campuzano, Oscar; Fernandez-Falgueras, Anna; Sarquella-Brugada, Georgia; Cesar, Sergi; Arbelo, Elena; García-Álvarez, Ana; Jordà, Paloma; Coll, Monica; Fiol, Victoria; Iglesias, Anna; Perez-Serra, Alexandra; Mates, Jesus; et al. (Frontiers in Genetics, 2019)
Cardiomyopathies are a heterogeneous group of inherited cardiac diseases characterized by progressive myocardium abnormalities associated with mechanical and/or electrical dysfunction. Massive genetic sequencing technologies allow a comprehensive genetic analysis to unravel the cause of disease. However, most identified genetic variants remain of unknown clinical significance due to incomplete penetrance and variable expressivity. Therefore, genetic interpretation of variants and translation into clinical practice remain a current challenge. We performed retrospective comprehensive clinical assessment and genetic analysis in six families, four diagnosed with arrhythmogenic cardiomyopathy and two diagnosed with hypertrophic cardiomyopathy. Genetic testing identified three rare variants (two nonsense and one small indel inducing a frameshift), each present in two families. Although each variant is currently classified as pathogenic and the cause of the diagnosed cardiomyopathy, the onset and/or clinical course differed in each patient. New genetic technology allows comprehensive yet cost-effective genetic analysis, although genetic interpretation and clinical translation of identified variants should be carefully done in each family in a personalized manner.